Breach of Psychological Contract and Customer Behavior to Reuse Retailing Website: A Multiple Mediation Approach - Tyaz Nugraha, Andhyka; Ratnawati, Elfrida; Lanontji, Muryanto; Hakimah, Yusro (International Journal of Psychosocial Rehabilitation, 2020)
The process of psychological contract breach (PSYCB) is largely studied in the literature of organizational behavior which states that PSYCB has negative impact on attitudes of employees such as job satisfaction and trust. As the psychological states affect behavior, it is significant to test how PSYCB may influence satisfaction and trust in the environment of online retailing. The purpose of this paper is to study the mediating role of customer trust (CSTR) and customer satisfaction (CSST) in the linkage between customer intention to reuse online retailing website (CIRU) and PSYCB. The survey of the current study was directed on the postgraduate students. The respondents were studying in Chiang Mai University in Thailand. The sample (321) participants’ age ranged from 19 to 26 because it was the highest level of penetration of internet in the Thailand and this age group individuals were more likely to buy online. PSYCB and CIRU are used as independent and dependent variables, respectively. While CSTR and CSST are used as mediating variables. The mediation of CSST and CSTR is tested using the method of bootstrapping. For the association between CSST and CSTR as well as mediating impacts of CSTR and CSST on the interaction between PSYCB and CIRU, the study analyzed for multiple mediation. The findings show that PSYCB has negative influence on CSTR, CSST and CIRU. CSTR is directly associated with CSST. The impact of CSTR on CIRU and CSST on CIRU are also found to be positive. The findings also show that CSTR partially mediates the relationship between PSYCB and CIRU and CSST also marginally mediates the linkage between PSYCB and CIRU. The results also show that CSST marginally mediates the association between CSTR and CIRU and CSTR partially mediates the link between PSYCB and CSST. Moreover, CSTR and CSST together fully mediate the relationship between PSYCB and CIRU. The study recommends that PSYCB should be reduced for successful online retailing as PSYCB negatively influence CSTR and CSST of e-buyers which in turn affect the buyer’s intention to reuse online retailer’s website.